Total Synthesis of jerantinine alkaloids and a biocatalytic synthesis of 2,6 - Disubstituted tetrahydropyrans using an alcohol dehydrogenase - Eastman, H (2020)
This thesis is comprised of two sections; The first is a semi synthesis of the cytotoxic natural product jerantinine A. Starting from the natural product tabersonine, isolated from Voacanga africana, which contains the 3 stereocenters present in jerantinine alkaloids set in the correct conformation. The reaction conditions were optimised and produced jerantinine A from tabersonine in a 16% yield over 7 steps. Following this, the biological activity was evaluated using MCF-7 Cancer cell lines, a clonogenic assay, cell cycle analysis and a tubulin polymerisation assay. These results concluded that jerantinine A was a tubulin destabilising agent and were visualised using confocal microscopy.